UNSTABLE ANGINA: SPECIFIC FEATURES OF PATHOGENESIS AND TREATMENT - S. A. Chernov (Российский кардиологический журнал, 2002)
We have analyzed the results of treatment of 1325 patients with unstable angina, all men aged 35 to 75. All pateitns received a standard of intensive treatment with aspirin, infusion of nitroglycerin and heparin or LMWH and the usage of b-blockers. Arrhythmias required antiarrhythmic treatment including electrical procedures. ST segment elevation or newly emerged LBBB (acute coronary syndrome) required thrombolysis. Treatment yielded good results in 862 patients (65%), satisfactory in 195 (14.5%) and unsatisfactory in 132 (10%). 66 patients (5%) had ineffective conservative treatment, myocardial infarction developed in 70 (5.5%), of which 3 died (2%).34 patients with critical one- or two-vessel disease underwent PTCA and stenting with good short-term result, just one of them developed a non-fatal MI during the procedure. 125 patients underwent autovenous coronary bypass of which the short-term results were as follows: non-fatal MI in 6 (4.5%), post-surgery death in 3 (2.4%). Angina seized in 103 of 116 patients (89%). The best short-term results were observed in patients stabilized by the time of intervention.